From Sweeping to the Caress: Similarities and Discrepancies between Human and Non-Human Primates’ Pleasant Touch - Grandi, Laura C. (Frontiers in Psychology, 2016)
Affective touch plays a key role in affiliative behavior, offering a mechanism for the formation and maintenance of social bonds among conspecifics, both in humans and non-human primates. Furthermore, it has been speculated that the CT fiber system is a specific coding channel for affiliative touch that occurs during skin-to-skin interactions with conspecifics. In humans, this touch is commonly referred to as the caress, and its correlation with the CT fiber system has been widely demonstrated. It has been hypothesized that the sweeping touch that occurs during grooming in non-human primates may modulate the CT fibers, with recent preliminary studies on rhesus monkeys supporting this hypothesis. The present mini-review proposes a comparison between the pleasant touch, caress and sweeping of humans and non-human primates, respectively. The currently available data was therefore reviewed regarding i) the correlation between pleasant touch and CT fibers both in humans and non-human primates, ii) the autonomic effects, iii) the encoding at the central nervous system, iv) the development from early life to adulthood, and v) the potential applications of pleasant touch in the daily lives of both humans and non-human primates. Moreover, by considering both the similarities and discrepancies between the human caress and non-human primate sweeping, a possible evolutionary mechanism can be proposed that has developed from sweeping as a utilitarian action with affiliative meaning among monkeys, to the caress as a purely affective gesture associated with humans.